Preparation method of high-temperature-resistant antioxidant chopped carbon fiber reinforced ceramic-based composite material
By surface modification of chopped carbon fiber and mechanical activation of ceramic matrix materials, combined with uniform dispersion technology, electromagnetic field-assisted stirring and gradient heating sintering and other processes, the surface oxidation and interface bonding of traditional composite materials in high-temperature environments is solved. The problem is that the material has significantly improved its high temperature oxidation resistance and mechanical properties.
Patent Information
- Application Number
- CN202411364621.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-02-11
AI Technical Summary
The traditional method of preparing chopped carbon fiber reinforced ceramic matrix composites has problems such as surface oxidation, insufficient interface bonding, and insufficient material density in high-temperature environments, making it difficult to meet the high performance requirements under complex working conditions.
Short-cut carbon fibers are treated with surface modification and SiC coating is applied to improve oxidation resistance; ceramic matrix materials are mechanically activated to improve sintering activity; fiber orientation is optimized through uniform dispersion technology and electromagnetic field-assisted stirring process; gradient heating sintering is used and thermal isostatic treatment to improve material density and mechanical properties.
It significantly improves the high temperature oxidation resistance, mechanical properties and density of composite materials, and extends the service life of the material under harsh working conditions.
Smart Images

Figure CN119409516A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic matrix composite material preparation, and in particular to a method for preparing a high temperature resistant and oxidation resistant chopped carbon fiber reinforced ceramic matrix composite material. Background Art
[0002] Chopped carbon fiber reinforced ceramic matrix composites are widely used in aerospace, automotive engines and thermal protection materials, mainly due to their excellent high-temperature oxidation resistance, low density and good mechanical properties. However, the traditional preparation process mostly uses conventional surface treatment and ordinary hybrid molding technology, which cannot cope with the growing high-performance requirements. With the improvement of material performance requirements, such as higher oxidation resistance, heat resistance and mechanical strength, the problems of insufficient surface modification, insufficient matrix-fiber bonding and low material density in traditional methods are becoming more and more prominent. In order to meet the performance requirements under complex working conditions, the development of more advanced process technologies, such as fiber surface modification, matrix activation, orientation optimization and post-processing, has become the technical development direction to solve these problems. The traditional preparation method of chopped carbon fiber reinforced ceramic matrix composites has limitations in many key links, resulting in obvious deficiencies in practical applications. First, the chopped carbon fiber in the traditional method is usually not fully surface treated and directly mixed with the ceramic matrix. In a high temperature environment, the untreated carbon fiber surface is easily oxidized, especially in oxygen or other oxidizing atmospheres, the carbon fiber will undergo thermal oxidation reaction, resulting in a significant decrease in the mechanical properties of the fiber. The oxidation reaction not only weakens the strength of the carbon fiber itself, but also destroys the interfacial bonding force between the fiber and the ceramic matrix, resulting in interface failure, which ultimately affects the overall performance of the composite material. Secondly, the ceramic matrix material is usually not activated in the traditional preparation method, resulting in insufficient bonding between it and the chopped carbon fiber during the sintering process. During the sintering process, ceramic materials usually require higher temperatures and longer sintering cycles to achieve higher density, but unactivated ceramic particles are prone to produce pores or irregular microstructures during sintering. These pores not only weaken the mechanical properties of the material, but also lead to poor thermal shock resistance of the composite material, especially in extreme temperature change environments, the material is more likely to crack or break. In addition, the traditional mixing and molding process technology is relatively simple, and it is difficult to achieve uniform dispersion and optimized orientation of chopped carbon fibers in the ceramic matrix. Usually, mechanical stirring or ordinary mixing methods are used, and it is difficult to ensure that the fibers are arranged in the expected direction, resulting in large differences in the anisotropic properties of the composite material. The uneven distribution of fibers in the material will cause local stress concentration, resulting in weaknesses in the overall mechanical properties and thermal stability of the material, affecting its reliability under high temperature or mechanical load environments. In addition, the lack of fine temperature gradient control during the sintering process often leads to uneven internal structure of the material, affecting the degree of densification, further limiting the overall performance of the material, which needs to be optimized and improved. Summary of the invention
[0003] The purpose of the present invention is to solve the technical problems raised in the above background technology.
[0004] The present invention adopts the following technical solution: a method for preparing a high temperature resistant and oxidation resistant short carbon fiber reinforced ceramic matrix composite material, comprising the following steps:
[0005] S1: Selection and surface treatment of reinforcing fibers: Chopped carbon fibers are selected as reinforcing materials and surface modified to improve their oxidation resistance under high temperature conditions and the interfacial bonding strength with the ceramic matrix;
[0006] S2: Selection and pretreatment of ceramic matrix materials: Select ceramic matrix materials and activate or modify them to improve the sintering activity of the matrix materials and their bonding ability with the reinforcing fibers;
[0007] S3: Mixing treatment: Mix the surface treated chopped carbon fibers with the pretreated ceramic matrix material, and use uniform dispersion technology or mechanical stirring process to fully disperse the two materials and form a uniform mixture;
[0008] S4: Orientation adjustment: Optimize the orientation distribution of chopped carbon fibers in the mixture through physical or chemical means to improve the mechanical and thermal properties of the composite material;
[0009] S5: Molding: Molding the mixture, using a molding, injection or extrusion process, to prepare a composite material preform with a predetermined shape;
[0010] S6: Drying and curing treatment: The preform is dried and preliminarily cured to remove the solvent and residual moisture in the mixture and enhance the initial mechanical strength of the material;
[0011] S7: Sintering treatment: In a protective atmosphere or vacuum environment, a high-temperature sintering treatment is performed in stages to densify the composite material and form a stable ceramic matrix structure;
[0012] S8: Post-treatment: According to the requirements of the composite material, the sintered material is subjected to mechanical post-treatment or surface coating treatment to further improve its oxidation resistance, wear resistance and mechanical properties.
[0013] Preferably, the length of the chopped carbon fiber in step S1 is 2 to 10 mm, and a layer of SiC coating is coated on its surface by chemical vapor deposition (CVD), and the coating thickness is 10 to 100 nanometers to improve its oxidation resistance in high temperature environments. Here, by coating a layer of SiC coating on the surface of the chopped carbon fiber, especially by chemical vapor deposition (CVD), the oxidation resistance of the carbon fiber in a high temperature environment is enhanced. This coating can not only effectively prevent the oxidation loss of carbon fiber at high temperature, but also improve the interface bonding strength between the fiber and the ceramic matrix, thereby improving the overall high temperature resistance and mechanical properties of the composite material, and extending the service life of the material under harsh working conditions.
[0014] Preferably, in step S2, the ceramic matrix material is silicon carbide, aluminum oxide or silicon nitride, and the ceramic powder is pretreated by mechanical activation, the ball milling time is 1 to 5 hours, and the powder particle size is 0.1 to 10 microns to improve the sintering activity. Here, the mechanical activation treatment of the ceramic matrix material can significantly improve the sintering activity of the ceramic powder. By refining the powder particle size through appropriate ball milling time, the particle surface activity can be effectively increased, thereby forming a denser composite material structure during the sintering process. Improve the degree of bonding between the ceramic matrix and the carbon fiber, reduce the pores and defects inside the material, and ultimately improve the mechanical strength and durability of the material.
[0015] Preferably, the mixing process in step S3 is carried out by ultrasonic dispersion method or high-speed stirring method, and the mixing time is 20 to 60 minutes to ensure the uniform dispersion of chopped carbon fiber and ceramic matrix material, and the binder is silicone resin or phenolic resin. Here, the carbon fiber and ceramic matrix mixture is processed by ultrasonic dispersion method or high-speed stirring method, which can effectively ensure the uniform dispersion of chopped carbon fiber in the ceramic matrix. This uniform distribution can avoid the problem of fiber aggregation or uneven distribution, ensure the uniform performance of each part of the composite material, and then improve the compressive strength, thermal shock resistance and fatigue resistance of the overall material. In addition, the use of a suitable binder also helps to improve the bonding strength of the material.
[0016] Preferably, the orientation adjustment in step S4 is achieved by an electromagnetic field assisted stirring process, with an electric field strength of 1 to 5 kV / m, or a magnetic field strength of 0.01 to 0.5 T, so that the chopped carbon fibers are oriented along the electromagnetic field direction to improve the anisotropic mechanical properties of the composite material. Here, by using an electromagnetic field assisted stirring process, the chopped carbon fibers are arranged in an orderly manner along the electromagnetic field or magnetic field direction, which can significantly optimize the fiber orientation distribution. Reasonable fiber orientation can improve the anisotropic mechanical properties of the composite material, especially the tensile strength and bending strength in a specific direction. This process ensures the stability and reliability of the composite material in practical applications, and is particularly suitable for fields with high requirements for mechanical properties.
[0017] Preferably, the molding pressure of the compression molding in step S5 is 50 to 150 MPa, the vacuum degree under vacuum conditions is 0.01 to 0.1 MPa, and the molding time is 5 to 20 minutes to ensure the compactness and uniformity of the preform. Here, during the molding process, the compression molding process combined with the vacuum conditions can significantly improve the compactness and uniformity of the preform. By reasonably controlling the molding pressure and time, the internal structure of the composite material is ensured to be tighter, thereby improving the overall mechanical properties and heat resistance of the material. Vacuum molding can also effectively reduce internal bubbles, reduce material defects caused by gas expansion during sintering, and make the composite material have higher density and reliability.
[0018] Preferably, the drying process in step S6 adopts a gradually increasing temperature drying strategy, with a preliminary drying temperature of 50 to 100°C and a time of 12 to 24 hours, followed by curing at 300 to 600°C to remove the solvent and enhance the initial mechanical properties of the material. Here, the gradual increase in temperature drying strategy helps to avoid cracks or stress concentration in the material due to rapid temperature increase during the drying process. By controlling the temperature and time of the preliminary drying and subsequent curing, the solvent and residual moisture can be fully removed, while the initial mechanical strength of the material can be enhanced. This drying process can reduce the stress in the preform, improve the integrity of the material and the stability of the subsequent sintering process.
[0019] Preferably, the sintering process in step S7 adopts a gradient temperature increase strategy, with a pre-sintering temperature of 1200 to 1500°C for 2 to 4 hours, and a main sintering temperature of 1600 to 2000°C for 4 to 8 hours to improve the densification of the composite material. Here, sintering by a gradient temperature increase strategy helps to gradually achieve the densification of the composite material at different temperature stages. In the pre-sintering stage, low temperature can remove residual gas and some organic matter in the material, reducing the formation of defects during the sintering process; high temperature in the main sintering stage further promotes the densification of the ceramic matrix. This strategy improves the microstructural uniformity of the material, and ultimately significantly enhances the mechanical properties, heat resistance and oxidation resistance of the composite material.
[0020] Preferably, the post-treatment in step S8 includes hot isostatic pressing (HIP) treatment of the composite material at a treatment temperature of 1500 to 1900°C, a pressure of 100 to 200 MPa, and a time of 1 to 3 hours to further improve the density, mechanical properties and oxidation resistance of the material. Here, through hot isostatic pressing (HIP) treatment, the density of the composite material can be further improved under high temperature and high pressure conditions, the pores and defects remaining inside can be eliminated, and the mechanical strength and toughness of the material can be significantly improved. HIP treatment can also improve the oxidation resistance and wear resistance of the composite material, and is particularly suitable for key components operating under high temperature and high pressure environments, such as aerospace, turbine engines and other fields. This process ensures the long-term reliability of the composite material under extreme working conditions.
[0021] Compared with the prior art, the advantages and positive effects of the present invention are:
[0022] 1. In the present invention, the surface of the chopped carbon fiber is modified, especially by coating the fiber surface with SiC coating by chemical vapor deposition (CVD), which effectively improves the oxidation resistance of the carbon fiber under high temperature conditions. This coating enhances the stability of the fiber, reduces the oxidation loss of the fiber at high temperature, and strengthens the interface bonding force between the fiber and the ceramic matrix, avoiding peeling or interface failure under high temperature environment, thereby ensuring the overall stability and service life of the material.
[0023] 2. In the present invention, after the ceramic matrix material is mechanically activated, activation sites are formed on the particle surface, which significantly improves the sintering activity of the material. This treatment ensures that the chopped carbon fibers and the ceramic matrix can be tightly combined during the sintering process, effectively avoiding pores or defects between the matrix and the fibers, thereby improving the density and mechanical properties of the composite material, and making the material show stronger thermal shock resistance and fatigue resistance in extreme environments.
[0024] 3. In the present invention, the electromagnetic field assisted stirring technology can optimize the orientation distribution of short carbon fibers in the mixture, ensure that the fibers are evenly distributed and arranged in a specific direction, thereby significantly improving the anisotropic mechanical properties of the composite material. At the same time, the use of a gradient temperature sintering process and subsequent hot isostatic pressing (HIP) treatment further improves the density and overall mechanical strength of the material, especially the stability under high temperature and severe mechanical stress, and enhances the material's oxidation resistance and wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The present invention provides a schematic diagram of the overall process of a method for preparing a high temperature resistant and oxidation resistant chopped carbon fiber reinforced ceramic matrix composite material. DETAILED DESCRIPTION
[0026] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
[0027] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways than those described herein. Therefore, the present invention is not limited to the specific embodiments of the following disclosure.
[0028] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the technical field.
[0029] Embodiment 1
[0030] The present invention provides a technical solution: a method for preparing a high temperature resistant and oxidation resistant short carbon fiber reinforced ceramic matrix composite material. First, short carbon fiber with a length of 6 mm is selected as a reinforcing material. The carbon fiber is treated by chemical vapor deposition (CVD) technology, and a layer of silicon carbide (SiC) coating with a thickness of 40 nanometers is coated on its surface. The coating can significantly improve the oxidation resistance of carbon fiber in a high temperature environment and prevent the fiber from being oxidized and lost during use. The ceramic matrix material is silicon carbide (SiC) powder with an average particle diameter of 5 microns. In order to improve its sintering activity, the matrix material is mechanically activated by a planetary ball mill for 3 hours, so that the surface of the ceramic particles has higher activity. Then, the treated short carbon fiber is mixed with the activated silicon carbide powder in a weight ratio of 1:5. During the mixing process, a high-speed mixer is used to stir for 30 minutes to fully mix the fiber and the matrix to ensure the uniform distribution of the fiber. After the mixing is completed, the electric field-assisted process is used to orient the short carbon fiber in a specific direction. Specifically, electromagnetic field assisted stirring is performed under the condition of an electric field strength of 3kV / m. This treatment method can make the fibers arranged in order in the mixture, thereby improving the anisotropic mechanical properties of the composite material. Subsequently, the mixture is placed in a mold and molded at a pressure of 100MPa under a vacuum of 0.05MPa for 10 minutes to form a preliminary preform. The preform after molding is dried at 80°C for 12 hours to ensure that the moisture and solvent inside the preform are fully removed. After drying, the preform is placed in an oven at 400°C for curing for 2 hours to further enhance the mechanical strength of the material. After that, the preform is subjected to a gradient temperature sintering treatment in an argon protective atmosphere. The temperature of the pre-sintering stage is 1300°C for 3 hours to remove the residual gas inside the material. The temperature of the main sintering stage is 1800°C for 5 hours to ensure the densification of the ceramic matrix. Finally, the sintered composite material is subjected to hot isostatic pressing (HIP) treatment. This step is carried out at a pressure of 150 MPa and a temperature of 1600°C for 2 hours. The density of the material is further improved by the hot isostatic pressing process, and the internal pores are eliminated, ultimately obtaining a carbon fiber reinforced silicon carbide ceramic matrix composite material with excellent high temperature resistance, oxidation resistance and mechanical properties.
[0031] Embodiment 2
[0032] A method for preparing a high temperature resistant and oxidation resistant short carbon fiber reinforced ceramic matrix composite material, wherein short carbon fiber with a length of 4 mm is selected as a reinforcing material, and a 20-nanometer thick silicon carbide coating is deposited on its surface by chemical vapor deposition (CVD) technology. The coating can effectively protect the carbon fiber from oxidation damage in a high temperature environment, and at the same time improve the interfacial bonding strength between the fiber and the matrix. The ceramic matrix material is alumina (Al2O3), and its particle diameter is 3 microns. In order to enhance its sintering activity, the alumina matrix material is mechanically activated by a ball milling device for 2 hours, so that more active sites are formed on the particle surface and the bonding ability between particles is increased. The treated carbon fiber is mixed with alumina at a weight ratio of 1:8, and an ultrasonic dispersion method is used for dispersion treatment for 45 minutes to ensure that the fiber and the matrix are fully and evenly mixed. After the mixture is prepared, electromagnetic field-assisted stirring is performed under a magnetic field strength of 0.2T to uniformly orient the short carbon fiber along the direction of the magnetic field. This process ensures the uniform distribution and optimized orientation of the fiber in the material, which helps to improve the tensile strength and bending resistance of the material. Next, the mixture was placed in a mold, and under a vacuum of 0.02 MPa, a pressure of 80 MPa was applied for compression molding for 15 minutes to form a uniform and dense preform. The preform was left to dry at room temperature for 24 hours, and then cured at 500 ° C for 2 hours. The drying and curing process ensures the full removal of solvents and residual moisture, and enhances the mechanical strength and stability of the material. The sintering process adopts a staged heating process, first pre-sintering at 1400 ° C for 3 hours, and then main sintering at 1900 ° C for 5 hours to ensure that the matrix material is fully densified. Finally, the sintered composite material was subjected to hot isostatic pressing (HIP) treatment at a pressure of 180 MPa, a processing temperature of 1700 ° C, and a time of 2 hours. The HIP treatment further improves the density and mechanical properties of the material, so that the material has excellent high temperature resistance and oxidation resistance.
[0033] Embodiment 3
[0034] A method for preparing a high-temperature resistant and oxidation-resistant short-cut carbon fiber reinforced ceramic matrix composite material, wherein short-cut carbon fibers with a length of 5 mm are selected, and a 30-nanometer-thick rare earth oxide (such as yttrium oxide Y2O3) coating is deposited on the surface by a CVD process. The coating is used to significantly improve the oxidation resistance of the carbon fibers at high temperatures and enhance the interfacial bonding strength between the carbon fibers and the ceramic matrix. The ceramic matrix material is silicon nitride (Si3N4) with a particle diameter of 0.5 microns. The matrix material is mechanically activated and ball milled for 4 hours to increase its sintering activity and the bonding force between the particles. Then, the treated carbon fibers are mixed with the silicon nitride matrix in a weight ratio of 1:6, and dispersed using ultrasonic dispersion technology for 30 minutes to ensure that the two are fully mixed. Next, an electromagnetic field-assisted process is used to adjust the fiber orientation, and the mixture is stirred under an electric field strength of 4 kV / m to ensure that the fibers are uniformly oriented. This process optimizes the distribution of the fibers in the material, significantly improving the anisotropic mechanical properties of the material. Subsequently, the mixture was placed in a mold and molded under vacuum at a pressure of 120 MPa for 10 minutes to form a high-density preform. The preform was first dried at 60°C for 24 hours to ensure sufficient evaporation of the internal moisture, and then cured at 300°C for 2 hours. Next, the preform was sintered under a nitrogen protective atmosphere. The sintering process adopted a gradient heating method. The temperature of the pre-firing stage was 1200°C for 2 hours, and then it was raised to 2000°C for the main firing stage for 6 hours to ensure sufficient densification of the ceramic matrix. Finally, plasma spraying was performed on the surface of the sintered composite material to apply a layer of aluminum oxide (Al2O3) coating with a thickness of 50 microns. This coating can further enhance the oxidation resistance and wear resistance of the material, especially for high-temperature wear environments. The resulting composite material has extremely high density, strength, high temperature resistance and oxidation resistance, and is suitable for use in high-temperature complex environments, such as aerospace, thermal protection equipment, etc.
[0035] The above description is only a preferred embodiment of the present invention and does not limit the present invention in other forms. Any technician familiar with the profession may use the technical content disclosed above to change or modify it into an equivalent embodiment with equivalent changes and apply it to other fields. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a high temperature resistant and oxidation resistant short carbon fiber reinforced ceramic matrix composite material, characterized in that: The following steps are involved: S1: Selection and surface treatment of reinforcing fibers: Chopped carbon fibers are selected as reinforcing materials and surface modified to improve their oxidation resistance under high temperature conditions and the interfacial bonding strength with the ceramic matrix; S2: Selection and pretreatment of ceramic matrix materials: Select ceramic matrix materials and activate or modify them to improve the sintering activity of the matrix materials and their bonding ability with the reinforcing fibers; S3: Mixing treatment: Mix the surface treated chopped carbon fibers with the pretreated ceramic matrix material, and use uniform dispersion technology or mechanical stirring process to fully disperse the two materials and form a uniform mixture; S4: Orientation adjustment: Optimize the orientation distribution of chopped carbon fibers in the mixture through physical or chemical means to improve the mechanical and thermal properties of the composite material; S5: Molding: Molding the mixture, using a molding, injection or extrusion process, to prepare a composite material preform with a predetermined shape; S6: Drying and curing treatment: The preform is dried and preliminarily cured to remove the solvent and residual moisture in the mixture and enhance the initial mechanical strength of the material; S7: Sintering treatment: In a protective atmosphere or vacuum environment, a high-temperature sintering treatment is performed in stages to densify the composite material and form a stable ceramic matrix structure; S8: Post-treatment: According to the requirements of the composite material, the sintered material is subjected to mechanical post-treatment or surface coating treatment to further improve its oxidation resistance, wear resistance and mechanical properties.
2. The method for preparing a high temperature resistant and oxidation resistant short carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: In step S1, the length of the short carbon fiber is 2 to 10 mm, and a layer of SiC coating is coated on its surface by chemical vapor deposition (CVD) method, and the coating thickness is 10 to 100 nanometers to improve its anti-oxidation performance in high temperature environment.
3. The method for preparing the high temperature resistant and oxidation resistant short carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: In step S2, the ceramic matrix material is silicon carbide, aluminum oxide or silicon nitride, and the ceramic powder is pretreated by mechanical activation, the ball milling time is 1 to 5 hours, and the powder particle size is 0.1 to 10 microns to improve the sintering activity.
4. The method for preparing a high temperature resistant and oxidation resistant short carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: The mixing process in step S3 is carried out by ultrasonic dispersion method or high-speed stirring method, and the mixing time is 20 to 60 minutes to ensure uniform dispersion of the chopped carbon fibers and the ceramic matrix material. The binder is silicone resin or phenolic resin.
5. The method for preparing a high temperature resistant and oxidation resistant short carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: The orientation adjustment in step S4 is achieved by an electromagnetic field assisted stirring process, with an electric field strength of 1 to 5 kV / m, or a magnetic field strength of 0.01 to 0.5 T, so that the short chopped carbon fibers are oriented along the electromagnetic field direction to improve the anisotropic mechanical properties of the composite material.
6. The method for preparing a high temperature resistant and oxidation resistant short carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: The molding pressure of the compression molding in step S5 is 50 to 150 MPa, the vacuum degree under vacuum conditions is 0.01 to 0.1 MPa, and the molding time is 5 to 20 minutes to ensure the compactness and uniformity of the preform.
7. The method for preparing a high temperature resistant and oxidation resistant short carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: The drying process in step S6 adopts a gradually increasing temperature drying strategy, with an initial drying temperature of 50 to 100° C. for 12 to 24 hours, followed by curing at 300 to 600° C. to remove the solvent and enhance the initial mechanical properties of the material.
8. The method for preparing the high temperature resistant and oxidation resistant short carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: The sintering process in step S7 adopts a gradient temperature increase strategy, with a pre-sintering temperature of 1200 to 1500° C. for 2 to 4 hours and a main sintering temperature of 1600 to 2000° C. for 4 to 8 hours to improve the densification of the composite material.
9. The method for preparing a high temperature resistant and oxidation resistant short carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: The post-treatment in step S8 includes hot isostatic pressing (HIP) treatment of the composite material at a temperature of 1500 to 1900° C., a pressure of 100 to 200 MPa, and a time of 1 to 3 hours to further improve the density, mechanical properties, and oxidation resistance of the material.
Citation Information
Patent Citations
Preparation method for high reliability large-scale silicon nitride ceramic material
CN101538162A
High-performance SiC ceramic-based composite material aero-engine blade manufacturing method
CN104529458A
Method for preparing carbon fiber reinforced silicon carbide (Csf / C-SiC) composite material
CN105967712A
Chopped carbon fiber toughened silicon carbide composite material and preparation method thereof
CN113121242A
Thermally conductive formed article and method of manufacturing the same
US20030194544A1
Cited By
Circuit board structure of aviation equipment
CN119697898A
Circuit board structure of aviation equipment
CN119697898B
Artificial board added with carbon fibers
CN119928031A
A carbon fiber-added wood-based panel
CN119928031B
Preparation method of carbon-ceramic composite material
CN120365047A